1978
DOI: 10.1111/j.1432-1033.1978.tb12123.x
|View full text |Cite
|
Sign up to set email alerts
|

The Reactivity of Sulfhydryl Groups at the Active Site of an R-Factor -Specified Variant of Chloramphenicol Acetyltransferase

Abstract: 1. The commonly observed type I variant of chloramphenicol acetyltransferase specified by R factors is a tetrameric enzyme and contains four half-cysteine residues per identical subunit.All four thiols are reactive when the protein has been reduced in the presence of 6 M guanidine-HC1. 2.Iodoacetamide is an effective inhibitor of native chloramphenicol acetyltransferase. The incubation of iodo[14C]acetamide with enzyme leads to amido-carboxymethylation. Chloramphenicol is effective in preventing both inactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1980
1980
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…The CAT enzyme catalyzes conversion of chloramphenicol and acetyl-CoA to 1,3-diacetoxy chloramphenicol and CoA in vivo (Lewendon et al, 1988;Shaw, 1983). In the absence of chloramphenicol, it has been reported that CAT has intrinsic thioesterase activity which can converts acetyl-CoA to acetate and CoA (Kleanthous and Shaw, 1984;Zaidenzaig and Shaw, 1978). Thus, we hypothesized that CAT was metabolically interacting with the reduced genome cells when the acetyl-CoA fluxes were not balanced with respect to synthesis and utilization.…”
Section: Inactive Cat Fed-batch Culturesmentioning
confidence: 99%
“…The CAT enzyme catalyzes conversion of chloramphenicol and acetyl-CoA to 1,3-diacetoxy chloramphenicol and CoA in vivo (Lewendon et al, 1988;Shaw, 1983). In the absence of chloramphenicol, it has been reported that CAT has intrinsic thioesterase activity which can converts acetyl-CoA to acetate and CoA (Kleanthous and Shaw, 1984;Zaidenzaig and Shaw, 1978). Thus, we hypothesized that CAT was metabolically interacting with the reduced genome cells when the acetyl-CoA fluxes were not balanced with respect to synthesis and utilization.…”
Section: Inactive Cat Fed-batch Culturesmentioning
confidence: 99%
“…Also, the chloramphenicol acetyltransferase protein can be easily purified by a single-step affinity-chromatography column (10) and is therefore readily available for physical and enzymatic characterization as well as for the production of antiserum. In addition, most of the amino acid sequence of the protein has been determined (20,21) and should provide a useful reference for comparative studies. Finally, it is possible to obtain, in yeast, mutants in which some aspect of either the expression of the cam r gene or the maintenance or replication of the plasrnid is altered.…”
Section: Discussionmentioning
confidence: 99%
“…The type I CAT has the unusual property of binding strongly to fusidic acid (406) and rosaniline dyes (302). The partial amino acid sequences of the type II and III enzymes are also known (275,440). The chromosomal enzyme of Proteus mirabilis is related to the type I variant (440).…”
Section: Inactivation Mechanismsmentioning
confidence: 99%
“…The partial amino acid sequences of the type II and III enzymes are also known (275,440). The chromosomal enzyme of Proteus mirabilis is related to the type I variant (440). CAT has also been found in nonenteric species of gram-negative bacteria.…”
Section: Inactivation Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation